The trouble with squads: accounting for corruption in Australia’s specialist policing units - Bleakley, Paul (Criminal justice studies, 2021)
The specialist squad is a common aspect of modern intelligence-led policing. Officers seconded to such units learn from the institutional knowledge and experience in a certain area of enforcement, allowing them to develop an expertise that enables proactive policing. While the utility of specialist squads is clear, the vulnerability of officers attached to them to become involved in corruption is also high. Corruption research argues that officers in squads are at risk of engaging in misconduct for a variety of reasons, such as the low visibility of their work and the necessity of building relationships with criminal actors. The history of police corruption in Australia supports this theory, with a range of examples of corruption in specialist squads to be found across the country. From an historical criminology perspective, this article explores the corruption in Australia’s specialist squads to discuss why risk factors were not addressed despite being consistently identified in the past. It also looks at attempts by police administrators and governments to deal with corruption in specialist squads, evaluating the efficiency of these strategies with a view to informing future anticorruption measures.